Pengaruh Literasi Keuangan, Persepsi Risiko, Dan Locus Of Control Terhadap Keputusan Investasi (Studi Kasus Pada Pegawai Di Kota Padang) - Hari Ashari; Reno Fithri Meuthia; Ferdawati Ferdawati (LP2M Politeknik Jambi, 2024)
This study aims to analyze the influence of financial literacy, risk perception, and locus of control on investment decisions among employees in Padang. Financial literacy refers to an individual's level of knowledge and understanding of financial concepts, while risk perception reflects their view of the potential losses they may face in investing. Locus of control refers to a person's beliefs about control over the outcomes they achieve, both from themselves and external factors. This research uses a quantitative approach with a survey method, by distributing questionnaires to 164 respondents who work as employees in Padang. The collected data were analyzed using multiple linear regression to determine the effect of each variable on investment decisions. The results showed that financial literacy, risk perception, and locus of control have a significant positive effect on investment decisions. The higher a individual's financial literacy, the better their ability to make investment decisions. Risk perception also has a positive effect, that individuals with good risk perception tend to be more careful in choosing investment products that suit their risk tolerance and making investment decisions. Individuals with a higher internal locus of control tend to be more active in financial planning and careful in choosing investment products that suit their financial goals.